Analyzing Design Principles of Biophilic Neighborhoods - Asadzadeh, Elham; Yousefi Ahmadchali, Maryam (Salehan Institute of Higher Education, 2018)
In current century, cities face rapidly evolving challenges, including climate change, resource shortages, population growth and urbanization, and financial pressures. Biophilic urbanism is an emerging design principle capable of considering the multidimensional and interdependent complexities of urban systems and infrastructure, which through the use of natural design features, can meet societyâs inherent need for contact with nature, and assist efforts to respond to these growing challenges. The purpose of this research is assessment Biophilic criteria in Iran metropolitan. In this research has been mentioned five criteria and 15 patterns. The quantitative and qualitative methods has been used. Data collection methods are observation and questionnaire. Also, has been used AHP method in order to comparison between criteria and patterns. Findings show the most important criteria is biodiversity in order to achieving biophilic neighborhood. Other principles are bio mimicry, prospect, and the sense of playfulness, enigmatic.